ANALISIS KUALITAS PELAYANAN ELECTRONIC-PROCUREMENT DI KABUPATEN PURBALINGGA - Cahyaningsih, Eva Nur; Lestari, Hesti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
The number of corruption cases in the procurement of goods / services of the Government raises the demand for the Government to innovate suppress the crime rate speed. One of the innovations undertaken by the Government is to develop their electronic-procurement services. However, the development of electronic-procurement services in several agencies are still not able to provide services to the maximum. The focus of this research is Quality Service-Procurement electronic Purbalingga. The purpose of this study to determine the quality of electronic-procurement services in Purbalingga and any aspects of the inhibitors. This research uses descriptive qualitative research. Data collection techniques using observation, interviews and documents related to the quality of electronic-procurement services in Purbalingga. The results showed that the quality of electronic-procurement services in Purbalingga has been good, although still hampered in some aspects, ease of access, control and affordability. Therefore, in this case need a strong effort from all stakeholders in improving the quality of service.